LINGUOCULTUROLOGICAL ASPECT OF COMPOUND WORDS: ENCODING CULTURAL IDENTITY (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Compound words serve as a bridge between language and culture, acting as a repository for a nation’s historical experience, social norms, and ecological environment. This article explores the linguoculturological aspect of compounding, focusing on how cultural meanings are embedded within lexical structures. By analyzing compounds through the lens of "cultural memory" and "linguistic worldview," the study demonstrates that the formation of compound words is rarely a random linguistic act but a culturally motivated process. The research highlights the role of national metaphors, traditional symbols, and social values in shaping the semantic core of compound units across different languages.